The Art Curator and Curation in The Works of Modern Researchers - Ivanovna Nekhvyadovich, Larisa; Vasilyevna Balakhnina, Lidiya; Valeryevna Chernyaeva, Irina (Opción, 2019)
The article presents an analytical review of the scientific literature on the topic of “curator” and “curation” in the art of the 21st century. Two direc- tions are identified: the works of Russian and foreign researchers. The authors of the article analyze and systematize monographs and research articles by curators, art historians, art critics, and researchers: B. and G.D. Lord, H.-U. Obrist, J. Rugg, M. Sedgwick, P. O’Neill, T. Smith, K. Schu- bert, M. Bhaskar, E.E. Prilashkevich, A.V. Karpov, V. Miziano, N.N. Suvo- rov. It is concluded that in the period from 2000 to 2017, researchers publis- hed numerous materials, devoted to the main concepts of the development of curation, the first manifestations of curation as an essential factor in the development of contemporary art, and the functions and forms of modern curation. Moreover, researchers investigate value orientations forming the main principles of the curator’s choice and the issues related to the study of an art project as the subject of research in contemporary humanitarian knowledge.